Unraveling the Composition of the Root-Associated Bacterial Microbiota of Phragmites australis and Typha latifolia - Pietrangelo, Laura; Bucci, Antonio; Maiuro, Lucia; Bulgarelli, Davide; Naclerio, Gino (Frontiers in Microbiology, 2018)
Phragmites australis and Typha latifolia are two macrophytes commonly present in natural and artificial wetlands. Roots of these plants engage in interactions with a broad range of microorganisms, collectively referred to as the microbiota. These interactions contribute to the natural process of phytodepuration, whereby pollutants are removed from contaminated water bodies through plants. The outermost layer of the root corpus, the rhizoplane, is a hot-spot for these interactions where microorganisms establish specialized aggregates designated biofilm. Earlier studies suggest that biofilm-forming members of the microbiota play a crucial role in the process of phytodepuration. However, the composition and recruitment cue of the Phragmites, and Typha microbiota remain poorly understood. We therefore decided to investigate the composition and functional capacities of the bacterial microbiota thriving at the P. australis and T. latifolia root-soil interface. By using 16S rRNA gene Illumina MiSeq sequencing approach we demonstrated that, despite a different composition of the initial basin inoculum, the microbiota associated with the rhizosphere and rhizoplane of P. australis and T. latifolia tend to converge towards a common taxonomic composition dominated by members of the phyla Acidobacteria, Actinobacteria, Firmicutes, Proteobacteria and Planctomycetes. This indicates the existence of a selecting process acting at the root-soil interface of these aquatic plants reminiscent of the one observed for land plants. The magnitude of this selection process is maximum at the level of the rhizoplane, where we identified different bacteria enriched in and discriminating between rhizoplane and rhizosphere fractions in a species-dependent and –independent ways. This led us to hypothesize that the structural diversification of the rhizoplane community underpins specific metabolic capabilities of the microbiota. We tested this hypothesis by complementing the sequencing survey with a biochemical approach and Scanning Electronic Microscopy demonstrating that rhizoplane-enriched bacteria have a bias for biofilm-forming members. Together, our data will be critical to facilitate the rational exploitation of plant-microbiota interactions for phytodepuration.